Research Trends and Perspectives on Psychiatric Nursing: A Decade of Progress and Challenges - Veolina Irman Veolina; Helena Patricia Helena; Dwi Christina Rahayuningrum Rahayuningrum Dwi Christina Rahayuningrum; Emira Apriyeni Emira (Frontiers on Healthcare Research, 2026)
Background: Psychiatric nursing continues to evolve in response to changing clinical, social, and professional demands, and the volume of research in this field has grown rapidly. This study aimed to analyse research trends and perspectives in psychiatric nursing over the last decade using bibliometric mapping and a thematic review. Methods: A bibliometric analysis was conducted using the Scopus database for publications indexed between 2015 and 2025, limited to English-language journal articles. Data were analysed with Scopus built-in tools and VOSviewer to identify publication trends, productive countries, institutions, journals, co-authorship networks, and keyword patterns. In addition, the 100 most-cited articles were reviewed to explore major thematic areas in psychiatric nursing. Results: The search initially retrieved 510 publications; after screening and duplicate removal, 236 articles were included in the final analysis. Publication output peaked in 2022, and the United States emerged as the leading contributor, followed by Australia and Iran. Key productive institutions included King’s College London and Turun yliopisto, while the Journal of Psychiatric and Mental Health Nursing was the most active journal. Thematic findings showed that recent psychiatric nursing research focused on interventions and patient outcomes, education and professional development, nurse–patient relationships and communication, technology integration, care for specific populations, and nursing theory in mental health. Conclusion: Psychiatric nursing research has expanded substantially and has become more interdisciplinary and patient-centred. However, persistent challenges remained, particularly in workforce preparedness, therapeutic communication, technological implementation, and support for nurses’ well-being. These findings provide a useful foundation for future research, education, policy, and psychiatric nursing practice.